(untitled) (International conference on multidisciplinary science, 2023)
museums are scientific, spiritual and educational treasures that deliver wealth Inherited from ancestors to the future generation. This treasure, which over the years will become rich and overflowing, will not only be a demonstration of cultural values, but also an invaluable book of speakers from the pages of a long history. Museums are a scientific, spiritual and educational treasure that supplies the wealth Inherited from ancestors to the future generation. This treasure, which over the years will become rich and overflowing, will not only be a demonstration of cultural values, but also an invaluable book of speakers from the pages of a long history.